Eight weeks of high-intensity interval vs. sprint interval training effects on overweight and obese adolescents carried out during the cool-down period of physical education classes: randomized controlled trial - González-Gálvez, Noelia; Soler-Marín, Antonio; Abelleira-Lamela, Tomás; Abenza-Cano, Lucia; Mateo-Orcajada, Adrián; Vaquero-Cristóbal, Raquel (Frontiers in Public Health, 2024)
Objective: The aim of this study was to evaluate the effect of sprint interval training (SIT) and (high intensive interval training (HIIT) carried out during the cool-down period of the physical education classes on body composition, blood pressure variables (BP) and pulse rate (PR)cardiovascular disease biomarkers, and cardiorespiratory fitness of adolescents who are overweight and obese, and to compare the differences in enjoyment in response to SIT vs HIIT. Methods: For this randomized controlled trialrandomized control trial, forty-five adolescents were recruited from a high school and were randomly placed into three groups. SIT and HIIT trained for 8 weeks, twice a week, for 12 minutes/session. Experimental group (EG) 3 was the control, and they maintained their regular physical education class schedule. The SIT group performed 6 sets of 60 seconds of work (90-95%HRmax) / 60 seconds of rest (50-55%HRmax), and the HIIT group performed 3 sets of 2 minutes of work (80-85%HRmax) / 2 minutes of rest (50-55%HRmax).Results: Both experimental groups showed a significant improvement in fat mass (FM) (%) and trunk FM (kg). In addition, EG2 reported a significance improvement in lean mass (kg), blood pressure body mass BP (mmHGBP) (mmHg), systolic blood pressure (SBP) (mmHg), diastolic blood pressure (DBP) (mmHg), pulse rate (PR) (bpm), LDL (mg/dL), HDL (mg/dL), LipidNonHDL (mg/dL), Chol / HDL (mg/dL) and VO 2 maxVo2máx (mLl/kg/min).